MiR‐204‐5p targeting SIRT1 regulates hepatocellular carcinoma progression. (October 2016) - Jiang, Guangbin; Wen, Li; Zheng, Hongmei; Jian, Zhiyuan; Deng, Weiping
Abstract : Hepatocellular carcinoma (HCC) is the most common type of cancer, which presents rapid tumor growth, drug resistance, and metastasis. Recently, microRNAs are shown to be involved in the cell biological processes in HCC, but the underlying molecular mechanisms remain unclear. This study aimed to investigate the cellular function and molecular mechanism of miR‐204‐5p in HCC. SIRT1 mRNA and miR‐204‐5p were examined by real‐time reverse transcription polymerase chain reaction. SIRT1 protein levels were measured by Western blotting. Cell proliferation assay was performed to confirm colony formation. Invasion assay was performed by transwell system. SPSS 15.0 for Windows was used for statistical analysis. SIRT1 was a potential oncogene in cancer, which was identified as a direct target of miR‐204‐5p. Overexpression of miR‐204‐5p in human HCC cell lines (BEL‐7405 and QGY‐7701) caused the suppression of cell survival ability, the increase of apoptosis, and drug sensitivity. SIRT1 was overexpressed in human HCC tissues and was negatively related to miR‐204‐5p levels. These results indicate that miR‐204‐5p and SIRT1 may play an important role in the development of HCC.